Variables Associated with Clinical Decision Making in the Treatment of Class I Malocclusion Patients - Hafsa Mahida; Sarwat Memon; Ali Kazi (ziauddin University, 2024)
Background: To achieve treatment goals in orthodontics, the decision to extract or not extract premolars meets with debate. This includes cephalometric findings and study-cast analysis as influencing factors. This research aimed to identify variables that aid in clinical decision-making in the treatment of Class 1 malocclusion patients. Methods: This was a retrospective study conducted on pre-treatment records of Class I patients. All patients had a Class I dental and skeletal malocclusion. A sample of n=80 patients was included (40 extraction cases, 40 non-extraction).  Cephalometric values and study-cast analysis for tooth-arch size discrepancy were performed and binary logistic regression was applied to run the univariate and multivariable analysis to investigate the association of different variables with extraction and non-extraction treatment. Odds ratio (OR) and 95% confidence intervals were reported and p <0.05 was considered statistically significant. Results: Univariate logistic regression showed that mandibular and maxillary crowding (p<0.001), overjet (p<0.001), SNGo (p= 0.01), nasolabial angle (NL) (p= 0.02), lower anterior facial height (LAFH) (p= 0.03) and upper lip in plane (ULE) (p= 0.05) had a significant association with the extraction and non-extraction groups. Hence, final multivariable logistic regression revealed that crowding (p< 0.01, 0.02), overjet (p= 0.009) and NL angle (p= 0.56) showed significant difference between the groups treated with and without extraction (p <0.05). Conclusion: The level of crowding in both the arches, the incisal overjet, and the nasolabial angle aid in the clinical decision-making for Class I malocclusion patients in choosing an extraction or non-extraction plan.  Keywords: Extraction; Non-Extraction; Class I; Malocclusion; Patients; Orthodontics.